THE GREEN ECONOMY: PRINCIPLES, BENEFITS, CHALLENGES, AND GLOBAL IMPLEMENTATION - Urunova Maftuna Gayratovna (Bright Mind Publishing, 2025)
The green economy is an economic development model that prioritizes sustainability, equity, and environmental preservation. This article explores the foundational principles of the green economy, its benefits and challenges, and examines global initiatives and case studies that illustrate its implementation. By analyzing various aspects of the green economy, the article aims to provide a comprehensive understanding of its potential to drive sustainable development and address pressing environmental issues.
Keywords: Green economy, sustainability, renewable energy, environmental policy, circular economy, climate change, sustainable development, green jobs, ecological economics, global initiatives.